Land fraud in multiple sales and foreclosure actions in housing development projects: A case study of abandoned housing project in Peninsular Malaysia - Md Dahlan, Nuarrual Hilal (2013)
Land frauds are common today. Land frauds include frauds committed by housing developers to the detriment of purchasers.It is the view of the author that examples of land fraud in housing development projects are multiple sales of the same housing units by vendor developers and technicalities in the law of foreclosure which have caused unfair losses to purchasers, particularly in abandoned housing projects.The objective of this paper via multiple sales and foreclosure proceedings. This paper is a result of a research using legal and qualitative research methodology. This paper finds that there are certain ways that housing developers can commit fraud in the housing transactions.One of the reasons as to why this fraud can be committed is due to the flows in the law governing housing transactions. At the end of this paper, the author suggests certain ways to prevent the commission of frauds in housing transactions.